Lidocaine Inhibits Rat Prostate Cancer Cell Invasiveness and Voltage-Gated Sodium Channel Expression in Plasma Membrane - Rizaner, Nahit; Fraser, Scott P.; Gül, İlknur Bugan; Purut, Esma; Djamgoz, Mustafa B. A.; ALTUN, SEYHAN (Springer, 2024)
There is increasing evidence, mostly from breast cancer, that use of local anaesthetics during surgery can inhibit disease recurrence by suppressing the motility of the cancer cells dependent on inherent voltage-gated sodium channels (VGSCs). Here, the possibility that lidocaine could affect cellular behaviours associated with metastasis was tested using the Dunning cell model of rat prostate cancer. Mostly, the strongly metastatic (VGSC-expressing) Mat-LyLu cells were used under both normoxic and hypoxic conditions. The weakly metastatic AT-2 cells served for comparison in some experiments. Lidocaine (1-500 mu M) had no effect on cell viability or growth but suppressed Matrigel invasion dose dependently in both normoxia and hypoxia. Used as a control, tetrodotoxin produced similar effects. Exposure to hypoxia increased Nav1.7 mRNA expression but VGSC alpha protein level in plasma membrane was reduced. Lidocaine under both normoxia and hypoxia had no effect on Nav1.7 mRNA expression. VGSC alpha protein expression was suppressed by lidocaine under normoxia but no effect was seen in hypoxia. It is concluded that lidocaine can suppress prostate cancer invasiveness without effecting cellular growth or viability. Extended to the clinic, the results would suggest that use of lidocaine, and possibly other local anaesthetics, during surgery can suppress any tendency for post-operative progression of prostate cancer.
Keywords: Hypoxia; Invasion; Lidocaine; Prostate Cancer; Tetrodotoxin; Voltage-gated Sodium Channel